2019
DOI: 10.1111/jgs.15807
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hormone Replacement Therapy on Sarcopenia: Is It Real?

Abstract: See the Reply by https://doi.org/10.1111/jgs.15805.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 8 publications
0
4
1
Order By: Relevance
“…Bea and colleagues found that lean body mass loss was lower in the HRT intervention arms compared to controls at year 3 follow-up; however, the association reversed between years 3 and 6 of follow-up, suggesting no long-term benefit to HRT use on lean body mass. 3 Additionally, this study found no significant association between HRT use and falls. Another WHI analysis on sarcopenia compared women currently using HRT to nonusers in a sensitivity analysis and found no significant difference in the association with risk of fractures across groups.…”
Section: Reply To Effects Of Hormone Replacement Therapy On Sarcopenicontrasting
confidence: 53%
See 4 more Smart Citations
“…Bea and colleagues found that lean body mass loss was lower in the HRT intervention arms compared to controls at year 3 follow-up; however, the association reversed between years 3 and 6 of follow-up, suggesting no long-term benefit to HRT use on lean body mass. 3 Additionally, this study found no significant association between HRT use and falls. Another WHI analysis on sarcopenia compared women currently using HRT to nonusers in a sensitivity analysis and found no significant difference in the association with risk of fractures across groups.…”
Section: Reply To Effects Of Hormone Replacement Therapy On Sarcopenicontrasting
confidence: 53%
“…2 Another study by Sanders et al showed that the main concern in oral administration of vitamin D replacement is an increased risk of falls and fractures among the older population. 3 In this study the mean baseline vitamin D levels were higher than 20 ng/mL. Therefore, we would like to ask if falls were specifically evaluated in this study.…”
Section: Comment On Comparing Vitamin D Supplementation Versus Placebmentioning
confidence: 94%
See 3 more Smart Citations